Translocação de Co e Mo aplicados em diferentes épocas na cultura da soja - Moraes, Leila Maria de Freitas (2006)
This study evaluated the translocation of Co and Mo applied in different times on the development of soybeans, determining their presence in soybean root nodules, leaves and grains. The assay was done in Fazenda Canadá, located in Uberlândia, MG. The experimental design was randomized blocks with seven treatments and six repetitions. Each experimental unit had twelve 11-m long rows, and 0.45 m between plants, sown with cultivar BRSMG-68. Planting fertilization was 360 kg ha-1 of the formulation 00-20-10. The seeds were inoculated with 500g peat inoculum for 50 kg seeds and the sources of Co and Mo were cobalt chloride and sodium molybdate, respectively. The treatments consisted in the following micronutrient application times: 1) control (no application); 2) via seed; 3) stage V4; 4) stage V6; 5) stage R1; 6) stage R3; and 7) via seed and stage R3. The doses 2.5 g ha-1 Co and 80 g ha-1 Mo were used in the treatments 2, 3, 4, 5 and 6, whereas for treatment 7, 2.5 g ha-1 Co and 20 g ha-1 Mo were used in the seeds, and at stage R3 400 g ha-1 Mo was applied. Twenty plants in each plot were collected weekly, for 9 weeks, except for treatments 5 and 6. Collections in treatments 5 and 6 were done for 8 and 7 weeks, respectively. Pod harvest occurred after the beans were filled. Cobalt and Molybdenum translocation from leaves to nodules and grains, and characteristics such as nodule number and dry weight, nitrogen in the leaves and grain, grain protein and culture yield were evaluated. The major conclusions are: a) molybdenum, applied in the leaves translocates to the nodules and grains, and when applied later in the cycle, it promotes an increase on of its levels in the grains; b) application of cobalt and molybdenum on the leaves or seeds had no positive effect on nodulation, nor on leaf nitrogen contents, neither on yield, nor on soybean grain nitrogen or protein contents.